Low Ambient Temperature Exposition Impairs the Accuracy of a Non-invasive Heat-Flux Thermometer - Masè, Michela; Werner, Andreas; Putzer, Gabriel; Avancini, Giovanni; Falla, Marika; Brugger, Hermann; Micarelli, Alessandro; Strapazzon, Giacomo (Frontiers in Physiology, 2022)
Background. Indirect core body temperature (CBT) monitoring from skin sensors is gaining attention for in-field applications thanks to non-invasivity, portability, and easy probe positioning. Among skin sensors, heat-flux devices, such as the so-called Double Sensor (DS), have demonstrated reliability under various experimental and clinical conditions. Still, their accuracy at low ambient temperatures is unknown. In this randomized cross-over trial, we tested the effects of cold temperature exposition on DS performance in tracking CBT. Methods. Twenty-one participants were exposed to a warm (23.2 ± 0.4°C) and cold (−18.7 ± 1.0°C) room condition for 10 minutes, following a randomized cross-over design. The accuracy of the DS to estimate CBT in both settings was assessed by quantitative comparison with esophageal (reference) and tympanic (comparator) thermometers, using Bland-Altman and correlation analyses (Pearson’s correlation coefficient, r, and Lin’s concordance correlation coefficient, CCC). Results. In the warm room setting, the DS showed a moderate agreement with the esophageal sensor (bias = 0.09 (-1.51; 1.69) °C, r = 0.40 (p=0.069), CCC = 0.22 (-0.006; 0.43)) and tympanic sensors (bias = 2.74 (1.13; 4.35) °C, r = 0.54 (p<0.05), CCC = 0.09 (0.008; 0.16)). DS accuracy significantly deteriorated in the cold room setting, where DS temperature overestimated esophageal temperature (bias = 2.16 (-0.89; 5.22) °C, r=0.02 (0.94), CCC=0.002 (-0.05; 0.06)). Previous exposition to the cold influenced temperature values measured by the DS in the warm room setting, where significant differences (p<0.00001) in DS temperature were observed between randomization groups. Conclusion. DS accuracy is influenced by environmental conditions and previous exposure to cold settings. These results suggest the present inadequacy of the DS device for in-field applications in low-temperature environments and advocate further technological advancements and proper sensor insulation to improve performance in these conditions.